Performance analysis of contention‐based access periods and service periods of 802.11ad hybrid medium access control. Issue 3 (1st September 2014) - Hemanth, C.; Venkatesh, T.G.
Abstract : In this study, the authors present an analytical model for the contention‐based access periods (CBAPs) and service periods (SPs) as specified in the medium access control (MAC) layer of IEEE 802.11ad standards. The analytical model for CBAP is based on a two‐dimensional Markov chain which captures the hybrid nature of IEEE 802.11ad MAC. The Markov chain is used to obtain important metrics like MAC throughput and average frame service time. The SPs are modelled as a M/G/1 queueing system with vacations. Using this model, the delay experienced by packets is calculated. The accuracy of the analytical models is established by extensive simulation results. A brief insight into optimal allocation of SP and CBAP is also discussed.